Strategi Nalar Kritis dan Resiliensi Spiritual Kyai Menghadapi Disrupsi di Pondok Pesantren Darussalam Blokagung Banyuwangi - Fidyyah Himatul Ulya; Moh. Adzkiyaunuha (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The digital disruption era has brought significant challenges to traditional educational institutions, including Islamic boarding schools (Pesantren), particularly regarding the erosion of moral values and the shift in charismatic authority. This study explores the survival and adaptation strategies of PP Darussalam Blokagung in facing these challenges, focusing on the synergy between intellectual reasoning and spiritual fortitude. The purpose of this research is to analyze how the Kyai (religious leaders) construct critical thinking through traditional methods and build spiritual resilience as a mental shield for students against the negative impacts of digitalization. This study employs a qualitative descriptive method with a case study approach, utilizing observations and interviews at PP Darussalam Blokagung. The findings reveal that the Kyai implement a